DIFFERENCES IN THE EFFECTIVENESS OF THE ACTIVE ROM ASSIMILITIVELY EXTREMITY BOTTOM WITH A WARM COMPRESS AGAINST POSTOPERATIVE PATIENT FLATUS TIME WITH GENERAL ANESTHESIA - Prasetyo Hari; Tophan Heri Wibowo; Siti Haniyah (Jurnal Inovasi Penelitian, 2023)
Abstract Postoperative ileus or paralytic ileus is one of the postoperative problems that can arise after surgery. Nurses can take a role in providing non-pharmacological therapy to prevent postoperative complications. One of them is the provision of lower extremity assistive active ROM and warm compresses. This study aims to analyze the differences in the effectiveness of lower extremity assistive active ROM with warm compresses on the flatus time of postoperative patients under general anesthesia. The results showed that the flatus time of postoperative patients who were given the Lower extremity Assistive Active ROM intervention obtained an average value of 6.25 hours with a standard deviation of 1.77012, the minimum value of 4.00 hours and the maximum value of 9.00 hours, the flatus time of postoperative patients with general anesthesia. given the warm compress intervention, the average value was 14.62 hours with a standard deviation of 4.16133, the minimum value was 10.00 hours and the maximum value was 23.00 hours. Postoperative ileus or paralytic ileus is one of the data. Analysis of postoperative distention under general anesthesia after active support for leg ROM and warm compresses resulted in p value = 0.000. The difference in distension time in postoperative patients with general anesthesia between adjuvant active ROM in the lower extremities with warm compresses. Nurses can play a role in providing non-pharmacological therapy to prevent postoperative complications